Sensor Fusion of Leap Motion Controller and Flex Sensors using Kalman Filter for Human Finger Tracking - Godwin Ponraj Joseph Vedhagiri; Hongliang Ren (IAES International Journal of Robotics and Automation (IJRA), 2017)
In our daily life, we, human beings use our hands in various ways for most of our day-to-day activities. Tracking the position, orientation and articulation of human hands has a variety of applications including gesture recognition, robotics, medicine and health care, design and manufacturing, art and entertainment across multiple domains. However, it is an equally complex and challenging task due to several factors like higher dimensional data from hand motion, higher speed of operation, self-occlusion, etc. This paper puts forth a novel method for tracking the finger tips of human hand using two distinct sensors and combining their data by sensor fusion technique.